Biological mechanisms and possible primary prevention of depression - Kuo, Chih-Yun; Stachiv, Ivo (World journal of psychiatry, 2022)
Individuals with unipolar depressive disorder (UDD) are having an increased risk of death and development of dementia in later life. It is widely expected that in a near future UDD would be the leading cause of death; therefore, a primary inexpensive prevention of UDD will be of a great importance to the society. Several studies provide evidences supporting the positive effect of Mediterranean diet on a reduced risk for development of depression.
Keywords: Depression; Mediterranean diet; Unipolar depressive disorder; Primary prevention; Dementia